DNA Damage and Survival Time Course of Deinococcal Cell Pellets During 3 Years of Exposure to Outer Space - Kawaguchi, Yuko; Shibuya, Mio; Kinoshita, Iori; Yatabe, Jun; Narumi, Issay; Shibata, Hiromi; Hayashi, Risako; Fujiwara, Daisuke; Murano, Yuka; Hashimoto, Hirofumi; Imai, Eiichi; Kodaira, Satoshi; et al. (Frontiers in Microbiology, 2020)
The hypothesis called “panspermia” proposes an interplanetary transfer of life. Experiments have exposed extremophilic organisms to outer space to test microbe survivability and the panspermia hypothesis. Microbes inside shielding material with sufficient thickness to protect them from UV-irradiation can survive in space. This process has been called “lithopanspermia,” meaning rocky panspermia. We previously proposed sub-millimeter cell pellets (aggregates) could survive in the harsh space environment based on an on-ground laboratory experiment. To test our hypothesis, we placed dried cell pellets of the radioresistant bacteria Deinococcus spp. in aluminum plate wells in exposure panels attached to the outside of the International Space Station (ISS). We exposed microbial cell pellets with different thickness to space environments. The results indicated the importance of the aggregated form of cells for surviving in harsh space environment. We also analyzed the samples exposed to space from 1 to 3 years. The experimental design enabled us to get and extrapolate the survival time course to predict the survival time of Deinococcus radiodurans. Dried deinococcal cell pellets of 500 μm thickness were alive after 3 years of space exposure and repaired DNA damage at cultivation. Thus, cell pellets 1 mm in diameter have sufficient protection from UV and are estimated to endure the space environment for 2–8 years, extrapolating the survival curve and considering the illumination efficiency of the space experiment. Comparison of the survival of different DNA repair-deficient mutants suggested that cell aggregates exposed in space for 3 years suffered DNA damage, which is most efficiently repaired by the uvrA gene and uvdE gene products, which are responsible for nucleotide excision repair and UV-damage excision repair. Collectively, these results support the possibility of microbial cell aggregates (pellets) as an ark for interplanetary transfer of microbes within several years.